Kedudukan Hukum Pemegang Hak Atas Tanah Wilayah Pesisir Yang Berada Dalam Keadaan Melanggar Ketentuan Batas Sempadan Akibat Force Majeure - Sanjaya, I Made Yonathan Hadi; Santosa, Anak Agung Gede Duwira Hadi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024)DO - 10.24843/AC.2024.v09.i02.p05, 2024)
This written study aims to investigate and discuss the legal issues surrounding the protection of coastal landowners' rights against the loss of some rights due to force majeure and the legal status of land that is in a state of legal violation due to erosion and subsequent changes in border areas along the coast. since of this legal issue, the property cannot be used going forward since it is in breach of the statute governing the coastal border. The landowner undoubtedly feels disadvantaged as a result of these legal issues, even if the issues did not arise owing to the landowner's intentions or conduct. This article is normative research, backed by several conceptual and case-based approaches to law, as well as data gathering methods utilizing a card system. The findings of this study indicate that there are no rules that offer landowners legal protection when they discover that their property is in violation of the law in coastal border zones. Legally, the state has the ability to limit land rights owing to the regulations and penalties outlined in Articles 61 and 62 UUPR, which confirms that this is connected to zoning laws being broken. In light of this legal situation, it is crucial to update or reconstruct norms pertaining to the determination of coastal border boundaries, keeping in mind that abrasion—an event that occurs outside of the control of a human, in this case the landowner—can undoubtedly lead to changes in coastal border boundaries.